Biomarkers for Disease Severity in Children Infected With Respiratory Syncytial Virus: A Systematic Literature Review. (14th August 2020) - Öner, Deniz; Drysdale, Simon B; McPherson, Calum; Lin, Gu-Lung; Janet, Sophie; Broad, Jonathan; Pollard, Andrew J; Aerssens, Jeroen; ,
Abstract: Background: Clinical manifestations of respiratory syncytial virus (RSV) infection vary widely from mild, self-limiting illness to severe life-threatening disease. There are gaps in knowledge of biomarkers to objectively define severe disease and predict clinical outcomes. Methods: A systematic search was performed, 1945–March 2019 in databases Ovid Medline, Embase, Global health, Scopus, and Web of Science. Risk of bias was assessed using the Cochrane tool. Results: A total of 25 132 abstracts were screened and studies were assessed for quality, risk of bias, and extracted data; 111 studies met the inclusion criteria. RSV severity was correlated with antibody titers, reduced T and B cells, dysregulated innate immunity, neutrophil mobilization to the lungs and blood, decreased Th1 response, and Th2 weighted shift. Microbial exposures in respiratory tract may contribute to neutrophil mobilization to the lungs of the infants with severe RSV compared with mild RSV disease. Conclusions: Although a wide range of biomarkers have been associated with RSV disease severity, robust validated biomarkers are lacking. This review illustrates the broad heterogeneity of study designs and high variability in the definition of severe RSV disease. Prospective studies are required to validate biomarkers. Additional research investigating epigenetics, metabolomics, and microbiome holds promise for novel biomarkers.